Literature Review: Policy Strategies for Natural Resource Management and Conservation - Maulana Ibrahim, Afif; Sastrodiharjo, Istianingsih (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Research and identify the relationship between the components under study in conservation and demonstrate a significant correlation between them. In this study, a qualitative literature review methodology was used which involved a systematic process of studying, analyzing and synthesizing relevant literature. Findings from this study indicate that effective collaboration between various stakeholders, preservation of local customs, and implementation of supportive policies are critical factors in efforts to manage natural resource conservation. The research also highlights the importance of involving local communities, non-governmental organizations, government, and the private sector in conservation management. Local customs also play an important role in preserving natural resources. In addition, policies that support natural resource conservation management are needed, including regulation of resource use, habitat protection, management of conflicts between stakeholders, and integration of related policies. A limitation of this study is the subjectivity in the collection and interpretation of data in the selected literature. In addition, the study was based on an analysis of existing literature, so the results depend on the quality and quantity of literature available. Also, since this study used a literature review approach, no primary data collection was conducted. The recommendation for future research is to involve primary data and conduct field research to confirm the findings of this literature review.